Ex ante evaluation of a PES system: Safeguarding recreational environments for nature-based tourism. (May 2017) - Tikkanen, Jukka; Hokajärvi, Raili; Hujala, Teppo; Kurttila, Mikko
Abstract: This paper evaluates the potentials of landscape and recreational values trading (LRVT), a system of payments for ecosystem services, as a vehicle to simultaneously preserve recreational environments for the nature-based tourism business and enhance welfare in rural communities. Ruka-Kuusamo in northeastern Finland serves as a case region for the ex ante evaluation. A novel evaluation framework of the study focuses on technical feasibility, institutional context, and potential surplus of LRVT to ecosystem service provision and social capital. The evaluation data from four years action research comprise surveys and group interviews with ecosystem service providers (forest owners) and buyers (tourism entrepreneurs and tourists), complemented with newspaper articles, forest data, and meeting minutes of local authorities. The results show tension between general acceptance and practical readiness to start LRVT. Several institutional challenges need to be solved before adopting LRVT in the region. Ambiguous understanding on the impacts of forest management to landscape and recreation value, deeply institutionalised norms among the forestry community, and hidden agendas may make it difficult to achieve considerable and sustainable improvements in the quality of ecosystem services. This paper concludes with discussing elements of LRVT that may be functional and provide positive returns to recreation values of the area and to social capital inside the community. Several years of research intervention and public discussion have now resettled the network of local actors to a promising position that shows capacity to co-create functional local forest governance, including possibly a publicly or privately organised LRVT system. Highlights: A novel application of "Pillars of institutions" and "social capital". Recreation and landscape value is not an explicitly defined ecosystem service. Hidden agenda of "effective forestry" inhibites improvements in the recreation values. Tight national co-ordination of forestry community do not support local innovations. Integrated approach of local co-governance and PES is recommended as a solution.